Maximum product of spacings prediction of future record values - Grigoriy Volovskiy; Udo Kamps (Metrika, 2020)
A spacings-based prediction method for future upper record values is proposed as an alternative to maximum likelihood prediction. For an underlying family of distributions with continuous cumulative distribution functions, the general form of the predictor as a function of the estimator of the distributional parameters is established. A connection between this method and the maximum observed likelihood prediction procedure is shown. The maximum product of spacings predictor turns out to be useful to predict the next record value in contrast to likelihood-based procedures, which provide trivial predictors in this particular case. Moreover, examples are given for the exponential and the Pareto distributions, and a real data set is analyzed.
Keywords: F99; M20; 510; Point prediction; Cumulative hazard rate; Spacings; Maximum observed likelihood predictor; Upper record values; Exponential distribution; Pareto distribution